Characterization of fetal antigen 1/delta-like 1 homologue expressing cells in the rat nigrostriatal system: effects of a unilateral 6-hydroxydopamine lesion. - Rémy Liechti; Angélique D Ducray; Pia Jensen; Stefano Di Santo; Stefanie Seiler; Charlotte H Jensen; Morten Meyer; Hans Rudolf Widmer (PLoS ONE)
Fetal antigen 1/delta-like 1 homologue (FA1/dlk1) belongs to the epidermal growth factor superfamily and is considered to be a non-canonical ligand for the Notch receptor. Interactions between Notch and its ligands are crucial for the development of various tissues. Moreover, FA1/dlk1 has been suggested as a potential supplementary marker of dopaminergic neurons. The present study aimed at investigating the distribution of FA1/dlk1-immunoreactive (-ir) cells in the early postnatal and adult midbrain as well as in the nigrostriatal system of 6-hydroxydopamine (6-OHDA)-lesioned hemiparkinsonian adult rats. FA1/dlk1-ir cells were predominantly distributed in the substantia nigra (SN) pars compacta (SNc) and in the ventral tegmental area. Interestingly, the expression of FA1/dlk1 significantly increased in tyrosine hydroxylase (TH)-ir cells during early postnatal development. Co-localization and tracing studies demonstrated that FA1/dlk1-ir cells in the SNc were nigrostriatal dopaminergic neurons, and unilateral 6-OHDA lesions resulted in loss of both FA1/dlk1-ir and TH-ir cells in the SNc. Surprisingly, increased numbers of FA1/dlk1-ir cells (by 70%) were detected in dopamine-depleted striata as compared to unlesioned controls. The higher number of FA1/dlk1-ir cells was likely not due to neurogenesis as colocalization studies for proliferation markers were negative. This suggests that FA1/dlk1 was up-regulated in intrinsic cells in response to the 6-OHDA-mediated loss of FA1/dlk1-expressing SNc dopaminergic neurons and/or due to the stab wound. Our findings hint to a significant role of FA1/dlk1 in the SNc during early postnatal development. The differential expression of FA1/dlk1 in the SNc and the striatum of dopamine-depleted rats could indicate a potential involvement of FA1/dlk1 in the cellular response to the degenerative processes.